1987
DOI: 10.1088/0143-0815/8/2/003
|View full text |Cite
|
Sign up to set email alerts
|

Continuous 24 hour ambulatory monitoring of intragastric pH in man

Abstract: A system has been developed which permits continuous 24 hour ambulatory recording of intragastric pH under near-physiological conditions. The system utilises a Cecar combination pH electrode connected through a pre-amplifier to an Oxford Medical Systems Medilog 4-24 cassette recorder, and the pH recorded continuously on to tape. The data is replayed at high speed, digitised and then analysed. Sources of error included system drift, system noise and the effect of changes in electrode environment due to saliva, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…Such events have also been reported by others [5,8,10,15]. Little et al [16] believe these epi sodes of intense gastric alkalinization are due to duode nogastric reflux, a view shared by many authors [1.5, 15.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Such events have also been reported by others [5,8,10,15]. Little et al [16] believe these epi sodes of intense gastric alkalinization are due to duode nogastric reflux, a view shared by many authors [1.5, 15.…”
Section: Discussionsupporting
confidence: 55%
“…Information on 24-hour gastric and duodenal pH pro files from intraluminal monitoring in health and disease is limited. In most studies, only small cohorts of asymp tomatic volunteers have been studied by this method with the exception of one group that has intensively studied 24-hour gastric pH in 20-25 healthy volunteers [5][6][7], For this reason, comparable, normal values of 24-hour gastric pH remain to be established [8][9][10][11], There are even fewer studies of duodenal pH profiles. Most studies reported are short-term and only recently has 24-hour pH monitoring in the duodenum been investigated [12][13][14].…”
mentioning
confidence: 99%
“…Saliva could track down the electrode from the mouth and accumulate at its tip giving an alkaline or neutral pH reading but the electrodes we have used are mounted 5 mm proximal to the tip of the catheter. Kapur and associates [19] have also shown that tracking of saliva down the electrode cable or catheter has a minimal effect on pH.…”
Section: Discussionmentioning
confidence: 96%